2020
DOI: 10.1186/s12871-020-01139-y
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane modulates breast cancer cell survival via modulation of intracellular calcium homeostasis

Abstract: Background Some retrospective and in vitro studies suggest that general anesthetics influence breast cancer recurrence and metastasis. We compared the effects of general anesthetics sevoflurane versus propofol on breast cancer cell survival, proliferation and invasion in vitro. The investigation focused on effects in intracellular Ca2+ homeostasis as a mechanism for general anesthetic-mediated effects on breast cancer cell survival and metastasis. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…Significant differences were observed between groups, with propofol showing an inhibitory effect on signaling pathways involved in carcinogenesis [172]. Deng et al exposed breast cancer cell lines to sevofluorane vs. propofol, and observed an increase in tumor survival in the propofol group, mediated by the modulation of intracellular calcium homeostasis [173]. In contrast, Liu et al observed that sevoflurane suppressed breast cancer cell proliferation through an increase in miRNA-203 overexpression [174].…”
Section: Mirnas and Drugs Used During Anaesthetic Proceduresmentioning
confidence: 99%
“…Significant differences were observed between groups, with propofol showing an inhibitory effect on signaling pathways involved in carcinogenesis [172]. Deng et al exposed breast cancer cell lines to sevofluorane vs. propofol, and observed an increase in tumor survival in the propofol group, mediated by the modulation of intracellular calcium homeostasis [173]. In contrast, Liu et al observed that sevoflurane suppressed breast cancer cell proliferation through an increase in miRNA-203 overexpression [174].…”
Section: Mirnas and Drugs Used During Anaesthetic Proceduresmentioning
confidence: 99%
“…In a colorectal cancer cell line, desflurane (10.3%) induces EMT and metastasis through dysregulation of miR-34/LOXL3 axis a well-known tumor suppressor ( 64 ). Sevoflurane (2% for six hours), in vitro , increases survival of breast cancer cells via modulation of intracellular Ca 2+ homeostasis ( 65 ). Secondly, volatile anesthetics could facilitate cancer progression by inducing immunosuppression.…”
Section: Inhalational Agents and Intravenous Anesthetics For Cancer Surgerymentioning
confidence: 99%
“…Sevoflurane (2% for six hours), in vitro, increases survival of breast cancer cells via modulation of intracellular Ca 2+ homeostasis (65). Secondly, volatile anesthetics could facilitate cancer progression by inducing immunosuppression.…”
Section: Volatile Anestheticsmentioning
confidence: 99%
“…An interesting question remains whether the known effects of volatile anesthetics on immune function are detrimental for cancer recurrence and metastatic conversion. In vitro and in vivo studies have shown that when breast, ovarian and renal cell carcinoma cells are exposed to volatile gases there is increased cytokine release (IL-1/6/8 and TNF), NK and T-cell modulation as well as an increase in growth, angiogenic and migration factors ( 3 , 7 , 37 39 ). However, for other cancer types such as non-small cell lung cancer (NSCLC) exposure to volatile anesthetics has been shown to be suppressive of growth and migration ( 40 ).…”
Section: Tiva Vs Volatile Gas Anesthesiamentioning
confidence: 99%